A comparative study of postoperative acidemia after intraoperative administration of balanced crystalloid (Plasma-lyte A@) versus 0.9% sodium chloride in gastrointestinal surgery - Laxmi Narayan Dash,; Jagannath Panda,; Shibanee Jena,; Harikrishna Dalai,; Pritish Chandan Sahu,; Biswal, Debadas (Asian Journal of Medical Sciences, 2024)
Background: The administration of intravenous fluids is one of the most common and universal interventions in medicine. Fluid therapy is the most challenging and debated aspect of perioperative care. Plasma-lyte A® Injection (multiple electrolytes injection, type 1, USP) is indicated as a source of water and electrolytes or as an alkalinizing agent. 0.9% sodium chloride is an isotonic crystalloid solution having a sodium concentration higher is useful in replacing fluid and electrolyte loss. Aims and Objectives: The study was designed to compare the effects of intraoperative administration of balanced crystalloid solution (Plasma-Lyte A®) and 0.9% NaCl on acid-base balance in the post-operative period in patients undergoing gastrointestinal surgery. Materials and Methods: Eighty consenting patients of ASA-l and ASA-II who underwent Gastrointestinal surgery were at first randomly allocated to 2 groups. One group received Plasma-Lyte A® as the sole crystalloid and the other group received 0.9% sodium chloride. Results: Serum Na+ conc. of the groups were comparable and no difference was shown at the time of induction, but postoperatively at 12 h, there was a significant increase in group 2. There was no significant difference in serum K+ concentration in both the groups except at 6 h postoperatively when there was an increase in K+ concentration in group 1. Serum Cl− concentration was having no significant difference at the time of induction and 1 h intraoperative, but postoperatively at 1, 6, and 12 h the Cl− concentration significantly increased in group 2. HCO3− concentration of the two groups had no difference between them throughout the study period. The pH of patients in both the groups showed no statistically significant difference during the entire procedure (P>0.05). A significant decrease in pH observed in 0.9% sodium chloride group in comparison to Plasma-Lyte® group when the duration of surgery increased to more than 120 min. Conclusion: Both plasma-lyte A and 0.9% sodium chloride can be used safely as intravenous infusion fluid without altering pH status and blood electrolyte concentration in patients undergoing gastrointestinal surgery.